Workplace Psychological Violence Among junior Physicians Employed in an Egyptian University Hospital - Abdel-Aziz, Basem (International Journal For Research In Health Sciences And Nursing, 2019)
Workplace psychological violence (WPPV) is an organizational behavior problem. Study objectives were to determine the structure of WPPV, assess its prevalence, and identify high-risk categories among junior physicians in surgical and medical departments in an Egyptian university hospital. A self-administered questionnaire incorporating 45-item Leymann Inventory of Psychological Terror was used as an initial item pool to collect data. Exploratory factor analysis was used to identify a two-factor measurement model and confirmatory factor analysis – via structural equation modeling- was applied to assess its construct validity. Factorial validity was established thru global and local fit diagnostics. Convergent validity was demonstrated via adequate subscales alpha coefficients, composite reliabilities, variances extracted, and weight and significance of item loadings. Discriminant validity was verified by moderate interfactor correlations and subscales composite reliabilities were greater than average variance extracted. The validated model was used to determine the prevalence of WPPV, which proved to be (36.7 %). WPPV was more prevalent in surgical than medical departments. Females were less exposed to WPPV than males. Physicians with “very good” merit at M.B.Ch.B. were more exposed to WPPV than those with an “excellent” merit. Interventions and preventions in the form of policy, regulations, guidelines, and educational programs were recommended.